Pengaruh Latihan Jalan 6 Menit Terhadap Tingkat Kebugaran Pasien Pneumonia Ringan Dan Sedang Di RS Husada Utama Surabaya - Andriani, Dhita Wina; Endaryanto, Agung Hadi; Priasmoro, Dian Pitaloka; Abdullah, Ahmad (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Pneumonia is an acute inflammatory infection of the lung tissue or parenchyma or caused by various things, such as viruses, bacteria, parasites, or fungi. This study aims to detect the fitness of patients with mild and moderate pneumonia before and after doing 6 minutes of walking exercise. The independent variable in this study was 6-minute walking exercise , while the dependent variable was the fitness level of patients with mild and moderate pneumonia. This study has 30 respondents using purposive sampling. The design of this study was pre-experimental with a pre-and post-test design approach. The result in this study, the p-value = 0.000 (p<0.05) can guarantee that there is an effect of 6-minute walking exercise on the fitness level of patients with mild and moderate pneumonia at Husada Utama Hospital Surabaya in 2021